2019
DOI: 10.36551/2081-1160.2019.24.75-100
|View full text |Cite
|
Sign up to set email alerts
|

La Alquimista de los Sabores: Gastronomic Heritage, Gender, and the Tourist Imaginary in Mexico

Abstract: Through multi-sited fieldwork carried out in 2011 and 2014-17 in central Oaxaca and an analysis of secondary sources, this paper scrutinizes the rise of a culinary celebrity, Zapotec cook Abigail Mendoza Ruíz of Teotitlán del Valle, Oaxaca, in the broader context of a Mexican cultural politics of food as heritage. Focusing on food-related biography this essay reveals vernacular dynamics of heritagization of native foodways and the role renowned female cooks (cocineras) have played in this process. I scrutinize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
2
0
9
Order By: Relevance
“…She indicated that most maestras are close to the ruling local elites and some do not have a real background in traditional cooking, nor do they act as passers‐on of knowledge, as one may expect of a master. This echoes work in Oaxaca reporting that the prestigious position of maestra ‘does not solely depend on her skills and knowledge of regional cuisines, but rather on her socio‐economic status and connections […] as well as whether her skills and image can be exploited for commercial and promotional goals at a particular time’ (Hryciuk 2019: 91). After a period in which she resigned her identity as cocinera , Maria resumed with Encuentros in 2010 by invitation from the then Secretary of Tourism of Michoacán, a good patron of the restaurant.…”
Section: Control Dispossession and Resistancementioning
confidence: 80%
“…She indicated that most maestras are close to the ruling local elites and some do not have a real background in traditional cooking, nor do they act as passers‐on of knowledge, as one may expect of a master. This echoes work in Oaxaca reporting that the prestigious position of maestra ‘does not solely depend on her skills and knowledge of regional cuisines, but rather on her socio‐economic status and connections […] as well as whether her skills and image can be exploited for commercial and promotional goals at a particular time’ (Hryciuk 2019: 91). After a period in which she resigned her identity as cocinera , Maria resumed with Encuentros in 2010 by invitation from the then Secretary of Tourism of Michoacán, a good patron of the restaurant.…”
Section: Control Dispossession and Resistancementioning
confidence: 80%
“…Sin embargo, más allá del valor patrimonial de los alimentos, su consumo está determinado por: a) componentes biológicos (la palatabilidad y las sensaciones de hambre o saciedad), b) económicos (el costo, los ingresos y la disponibilidad en el mercado), c) físicos (el acceso, la zona geográfica, la educación, el estilo de vida o las capacidades personales -por ejemplo, para cocinar-y el tiempo disponible) y d) sociales (la cultura, la familia, y los patrones de alimentación) (Dip, 2014). De alguna forma, se incorporan los aspectos de la vida moderna a los hábitos alimenticios, marcando las pautas para nuevos estudios en comunidades que enfrentan procesos de transformación, en especial de cambio de roles en las mujeres guardianas del patrimonio gastronómico (Hryciuk, 2019;Matta, 2019).…”
Section: La Gastronomía Como Patrimonio Cultural Y Su Valor Comunitariounclassified
“…Los platillos e ingredientes comunican algo significativo sobre las personas, tanto al interior como al exterior de los grupos, a menudo en procesos socioculturales (Gatley, 2016). Este tipo de visión, ha provocado un creciente interés en la academia por el pasado y presente de los alimentos, así como por las prácticas asociadas con su producción, consumo y preservación, donde el rol de género condiciona esta actividad, no solo en México, sino en otras partes del mundo (Hryciuk, 2019;González, 2019;Matta, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Desde entonces ha aumentado el número de restaurantes, chefs y eventos que abogan por "el rescate y la conservación" de la cocina "tradicional" y la "gastronomía prehispánica" (Escofet Torres, 2013), así como la promoción de programas para apoyarlas. Instancias de gobiernos locales y federales animan a algunas mujeres a presentar sus cocinas "indígenas" como "arte culi-nario tradicional" en ferias para el turismo, ubicándolas en el centro de una tendencia gastronómica global y moderna en la que se reimaginan y representan comidas y alimentos endémicos, pero también a quienes las elaboran (Hryciuk, 2019;Suremain, 2019b;Jaramillo Navarro, 2020).…”
unclassified